Gambaran Tingkat Tekanan Darah Pada Warga Pondok Bambu - Haryo Ganeca Widyatama; Dietha Kusumaningrum; Alvina Dwi Susanti; Inayah Larang Asri; James Bernando Rajagukguk; Mesty Mela Safitri (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Blood pressure is the force exerted by blood against the walls of blood vessels and is generated by the pressure of blood against the walls of arteries when the blood is pumped from the heart to the tissues. Hypertension itself is a chronic condition that can persistently increase > 140/80 mmHg. Hypertension is also called the silent killer because hypertension sufferers are often unaware of the symptoms. Based on 2018 RISKESDAS data, the hypertension rate in the DKI Jakarta area is 10.17% and is the 6th largest province in Indonesia with hypertension patients. Based on the still high rate of hypertension in DKI Jakarta, especially East Jakarta, community service was carried out in the form of measuring blood pressure and administering blood pressure medication. The method used is mass treatment of residents whose blood pressure is measured as high. The nurse self-measured using a digital blood pressure monitor and after measuring it, the result was high blood pressure, so it was then recommended that you go to a general practitioner for a thorough examination. It was found that there was a high prevalence of blood pressure above normal (71.87%) consisting of 12 people (37.50%) with grade I hypertension and 11 people with grade II hypertension (34.37%). By knowing the picture of blood pressure levels, it is hoped that community empowerment can increase.